1995
DOI: 10.1093/arclin/10.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Children's color trails

Abstract: Color Trails for Children was developed in response to the need for instruments which minimize cultural bias in neuropsychological testing. The test, similar in format to Trail Making, was designed to provide an evaluation of speeded visuomotor tracking while minimizing the influence of language. The present research involves two exploratory studies which examine the relationship between Color Trails for Children and Trail Making, factors that may affect performance times, and discriminant validity. Results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 16 publications
1
25
0
1
Order By: Relevance
“…Colour errors, number errors, near-misses and prompts are also recorded; however, these errors are rare in a normative population. Williams et al (1995) found good correlations between the CCT and the TMT, good discriminant validity between normal control children and children with altered neuropsychological functions, and appropriate age-progression of scores.…”
Section: Comment [Jr1]: No Problemmentioning
confidence: 81%
“…Colour errors, number errors, near-misses and prompts are also recorded; however, these errors are rare in a normative population. Williams et al (1995) found good correlations between the CCT and the TMT, good discriminant validity between normal control children and children with altered neuropsychological functions, and appropriate age-progression of scores.…”
Section: Comment [Jr1]: No Problemmentioning
confidence: 81%
“…An adaptation of the Children's Color Trails Test (Williams et al, 1995) was used to evaluate executive functioning. In part A of the test, the participant had to connect a set of numbers in an ascending sequence (1 through 25) as quickly as possible.…”
Section: Background Cognitive Measuresmentioning
confidence: 99%
“…Color Trails is used to index executive functions, including sequencing and various attentional processes such as goal maintenance, response selection, shifting, and inhibition, using familiar stimuli (i.e., digits and colors) (Llorente, Williams, Satz, & D'Elia, 2003). It is intended to be a child-friendly, culture-free, and language-free version of the Trail Making Task (TMT) (Williams et al, 1995). The TMT has been used extensively in the neuropsychological literature as a measure of attentional flexibility and task switching that is particularly sensitive to frontal lobe dysfunction (Suchy, 2009).…”
Section: Introductionmentioning
confidence: 99%